An Epitome of Nonviolent Resistance: A Study of Gandhi’s The Story of My Experiments with Truth (Bon Voyage, 2019)
Truth and non-violence are the twin pillars on which rest the entire framework of the magnificent edifice of Mahatma Gandhi's glorious life and work. Gandhi names the protest satyagraha, which means the “force contained in truth and love,” or “nonviolent resistance.” The philosophy of satyagraha requires that a person who decides to break a law considered unjust must accept the consequences of that decision. Mahatma Gandhi, a determinant and an all committed human soul, ascends this material world and reigns in the hearts of billions and billions of people all around the world. The ideas of Mahatma Gandhi have had a lasting impact on crusades for rights and freedom: from the civil rights movement of the 1960s through the movements against corporate greed and racism that are developing today. This paper serves to locate some nonviolent resistances in reference to Mahatma Gandhi’s The Story of My Experiments with Truth.